2012
DOI: 10.1007/s00294-012-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

The Neurospora crassa chr-1 gene is up-regulated by chromate and its encoded CHR-1 protein causes chromate sensitivity and chromium accumulation

Abstract: The ChrA membrane protein belongs to the CHR superfamily of chromate ion transporters, which includes homologues from bacteria, archaea and eukaryotes. Bacterial ChrA homologues confer chromate resistance by exporting chromate ions from the cell's cytoplasm. The Neurospora crassa strain 74-A chr-1 gene encodes a putative CHR-1 protein of 507 amino acid residues, which belongs to the CHR superfamily. RT-PCR assays showed that expression of the chr-1 gene was up-regulated by chromate exposure of N. crassa cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…CHR-1 protein (homologous to ChrA) is present in several ascomycetes and other fungal phyla, such as Basidiomycota and Zygomycota, whereas CHR-1 is absent in the vast majority of yeasts (Flores-Alvarez et al, 2012). To our knowledge, Neurospora crassa is the only fungus in which a CHR-1 protein has been characterized (Flores-Alvarez et al, 2012). The expression of the CHR-1 gene was induced upon Cr(VI) exposure, but the encoded protein elicited the opposite effect as the expected.…”
Section: Chromate-resistance Determinants (Crds)mentioning
confidence: 99%
See 2 more Smart Citations
“…CHR-1 protein (homologous to ChrA) is present in several ascomycetes and other fungal phyla, such as Basidiomycota and Zygomycota, whereas CHR-1 is absent in the vast majority of yeasts (Flores-Alvarez et al, 2012). To our knowledge, Neurospora crassa is the only fungus in which a CHR-1 protein has been characterized (Flores-Alvarez et al, 2012). The expression of the CHR-1 gene was induced upon Cr(VI) exposure, but the encoded protein elicited the opposite effect as the expected.…”
Section: Chromate-resistance Determinants (Crds)mentioning
confidence: 99%
“…The expression of the CHR-1 gene was induced upon Cr(VI) exposure, but the encoded protein elicited the opposite effect as the expected. Instead of chromate tolerance, CHR-1 expression resulted in an increase in Cr(VI) sensitivity, indicating that it is a chromate transporter but promotes chromate accumulation inside the cell instead of extrusion (Flores-Alvarez et al, 2012). A possibility for the role of chromate uptake for the Chr-1 protein in N. crassa may be that the transported chromate is then destined for vacuolar compartmentalization.…”
Section: Chromate-resistance Determinants (Crds)mentioning
confidence: 99%
See 1 more Smart Citation
“…4C). This is consistent with previous studies that observed an increase in the expression levels of chrA and yieF after Cr(VI) treatment in pure bacteria or cells (Flores‐Alvarez et al ., 2012; Liu et al ., 2015). However, due to the severe degradation of RNA extracted by the original GTHE approach, the expressions of chrA and yieF were very low, and even showed downregulation after Cr(VI) treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the Neurospora crassa strain 74-A, chr-1 gene that encodes a putative CHR-1 protein and belongs to the CHR superfamily was identified [ 33 ]. However, contrary to the bacterial ChrA (chromate transport protein) homologues that confer chromate resistance by exporting chromate ions from the cell’s cytoplasm, the experimental data suggested that the N. crassa CHR-1 protein functions as a transporter that takes up chromate [ 34 ]. The presence of CHR-1 protein was reported to cause chromate sensitivity and chromium accumulation in N. crassa .…”
Section: Introductionmentioning
confidence: 99%